The direction of zakat accounting research: An analysis of the issues and implications of zakat institution management practice - Rusdianto Rusdianto (Universitas Negeri Surabaya, 2022)
Research on zakat accounting plays an essential role in the development process and zakat management practice. Many studies have discussed zakat management, including the process of zakat collection, management, distribution, and financial management. This research investigates various themes, findings, and approaches to give theoretical and practical contributions. This research uses the Systematic Literature Review (SLR) method. The review's focus is the publication of zakat accounting between 2009-2019. The search for research articles on zakat accounting is identified with relevant words such as Islamic accounting, zakat accounting, zakat performance, zakat governance, and zakat. The process consists of planning, conducting, and reporting. This research contributes in several ways. The first provides an analysis focused on zakat accounting research. The study results indicate that the theme widely discussed in zakat accounting research is the influence of accounting information, evaluation on zakat institution performance, zakat institution governance, management of zakat on business, zakat institution audit, and other issues. The second reveals the practices of zakat accounting at various zakat institutions. Finally, this research demonstrates the implications of zakat management practice and input for further zakat accounting research.